Resveratrol Supplementation Did Not Improve Cognition in Patients with Schizophrenia: Results from a Randomized Clinical Trial - Zortea, Karine; Franco, Viviane C.; Guimarães, Paula; Belmonte-de-Abreu, Paulo S. (Frontiers in Psychiatry, 2016)
Background: Schizophrenia is associated with psychotic experiences and cognitive deficits. Therefore, cognitive function is one of the most critical determinants of quality of life in this pathology. Resveratrol has been related with neuroprotective action but there are no studies evaluating resveratrol in schizophrenia. The objective of this study was to determine the efficacy of resveratrol supplementation on cognition in individuals with schizophrenia. Methods: This is a 1-month randomized, double-blind controlled trial (NCT 02062190), in which 19 men with diagnosis of schizophrenia, aged 18 to 65 years, were assigned to a resveratrol supplement group (200mg) or placebo group (200mg), with a 1-month follow-up. Applying a series of cognitive tests assessed neuropsychology performance (Hopkins Verbal Learning Test, Stroop Color and Word Test, Weschler Adult Intelligence Scale) and Brief Psychiatric Rating Scale assessed psychopathology severity. Results: There were no significant improvement in neuropsychology performance (episodic memory, working memory, attention and concentration capacity, inhibitory control, interference measures, selective attention and mental flexibility) and psychopathology severity after 1-month of resveratrol supplementation (p>0.05). Conclusion: In conclusion, we have shown that 1-month of a resveratrol supplementation (200 mg/day) did not improve episodic memory, working memory, attention and concentration capacity, inhibitory control, interference measures, selective attention and mental flexibility as compared with placebo in patients with schizophrenia.